2004
DOI: 10.1074/jbc.m400957200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of T-Loop and H-Motif Phosphorylation in the Regulation of S6 Kinase 1 by the Tuberous Sclerosis Complex

Abstract: The tuberous sclerosis gene products Tsc1 and Tsc2 behave as tumor suppressors by restricting cell growth, a function conserved among metazoans. Recent evidence has indicated that hyperactivation of S6 kinase 1 (S6K1) may represent an important biochemical change in the development of tuberous sclerosis-associated lesions. We show here that deletion of either Tsc1 or Tsc2 or expression of the Rheb (Ras homolog enriched in brain) GTPase leads to hyperphosphorylation of S6K1 at a subset of regulatory sites, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…In agreement with previous reports (26,30,38,45,64,68), we found that mTORC1 regulation by growth factors requires an intact TSC1/TSC2 complex, since cells deficient for Tsc1 or Tsc2 fail to downregulate mTORC1 function in response to serum deprivation, and rescue experiments restore mTORC1 sensitivity to serum withdrawal. Both growth factor and nutrient inputs are necessary for the full activation of mTORC1 in WT MEFs, whereas in MEFs lacking either Tsc1 or Tsc2 either input maintains partial or full mTORC1 activity.…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with previous reports (26,30,38,45,64,68), we found that mTORC1 regulation by growth factors requires an intact TSC1/TSC2 complex, since cells deficient for Tsc1 or Tsc2 fail to downregulate mTORC1 function in response to serum deprivation, and rescue experiments restore mTORC1 sensitivity to serum withdrawal. Both growth factor and nutrient inputs are necessary for the full activation of mTORC1 in WT MEFs, whereas in MEFs lacking either Tsc1 or Tsc2 either input maintains partial or full mTORC1 activity.…”
Section: Discussionsupporting
confidence: 81%
“…Collectively, these data suggest that tumor cells sensitive to mTOR inhibition are likely those with aberrant signaling through PI3K-Akt pathway such as those with activating mutations and/or amplification of growth factor receptors, PI3K, Akt, or through loss of PTEN [38][39][40] or TSC1/2. 41 Sensitive cells may be triggered to undergo G 1 arrest or apoptosis. The apoptotic effect may be determined, in part, by p53, p21 Cip1 , p27 Kip and bcl-2 function.…”
Section: Determinants Of Sensitivity and Resistance To Mtor Inhibitionmentioning
confidence: 99%
“…In TSC1/2-null cells and in cells ectopically expressing Rheb, S6K1 is highly active and yet remains sensitive to rapamycin (11,19,21,30,36,47). In fact, by virtue of its TOS motif and C-terminal tail, S6K1 is a direct substrate of Raptor-mTOR, which phosphorylates T389 within the S6K1 hydrophobic motif (1).…”
Section: S6k1 Acts Genetically Downstream Of Rheb Andmentioning
confidence: 99%
“…This is remarkably overt in cell-based and animal models of the tumor predisposition syndrome, tuberous sclerosis, wherein loss-of-function of the TSC1-TSC2 complex gives rise to pathological hyperactivation of mTOR and S6K (7,11,19,20,36,45,47) and produces cell-autonomous insulin resistance (13,20,32,39). In mouse embryo fibroblasts (MEFs) derived from TSC1-or TSC2-deficient animals, IRS1 and IRS2 are transcriptionally repressed (13,39) through a mechanism requiring S6Ks (13).…”
mentioning
confidence: 99%